Plant's-eye view of temperature governs elevational distributions - Liancourt, Pierre; Song, Xin; Macek, Martin; Santrucek, Jiri; Dolezal, Jiri (Global change biology, 2020)
Explaining species geographic distributions by macroclimate variables is the most common approach for getting mechanistic insights into large-scale diversity patterns and range shifts. However, species' traits influencing biophysical processes can produce a large decoupling from ambient air temperature, which can seriously undermine biogeographical inference. We combined stable oxygen isotope theory with a trait-based approach to assess leaf temperature during carbon assimilation (TL ) and its departure (ΔT) from daytime free air temperature during the growing season (Tgs ) for 158 plant species occurring from 3,400 to 6,150 m a.s.l. in Western Himalayas. We uncovered a general extent of temperature decoupling in the region. The interspecific variation in ΔT was best explained by the combination of plant height and δ13 C, and leaf dry matter content partly captured the variation in TL . The combination of TL and ΔT, with ΔT contributing most, explained the interspecific difference in elevational distributions. Stable oxygen isotope theory appears promising for investigating how plants perceive temperatures, a pivotal information to species biogeographic distributions.
Keywords: carbon stable isotope ratio; listy rostlin; mountain; uhlík; Temperature; oxygen stable isotope ratio; Oxygen Isotopes; plant height; temperature; teplota; leaf dry matter content; roční období; Seasons; izotopy kyslíku; biophysical traits; Carbon; decoupling; Plant Leaves